The Drosophila homologue of the amyloid precursor protein is a conserved modulator of Wnt PCP signaling. - Alessia Soldano; Zeynep Okray; Pavlina Janovska; Kateřina Tmejová; Elodie Reynaud; Annelies Claeys; Jiekun Yan; Zeynep Kalender Atak; Bart De Strooper; Jean-Maurice Dura; Vítězslav Bryja; Bassem A Hassan (PLoS Biology)
Wnt Planar Cell Polarity (PCP) signaling is a universal regulator of polarity in epithelial cells, but it regulates axon outgrowth in neurons, suggesting the existence of axonal modulators of Wnt-PCP activity. The Amyloid precursor proteins (APPs) are intensely investigated because of their link to Alzheimer's disease (AD). APP's in vivo function in the brain and the mechanisms underlying it remain unclear and controversial. Drosophila possesses a single APP homologue called APP Like, or APPL. APPL is expressed in all neurons throughout development, but has no established function in neuronal development. We therefore investigated the role of Drosophila APPL during brain development. We find that APPL is involved in the development of the Mushroom Body αβ neurons and, in particular, is required cell-autonomously for the β-axons and non-cell autonomously for the α-axons growth. Moreover, we find that APPL is a modulator of the Wnt-PCP pathway required for axonal outgrowth, but not cell polarity. Molecularly, both human APP and fly APPL form complexes with PCP receptors, thus suggesting that APPs are part of the membrane protein complex upstream of PCP signaling. Moreover, we show that APPL regulates PCP pathway activation by modulating the phosphorylation of the Wnt adaptor protein Dishevelled (Dsh) by Abelson kinase (Abl). Taken together our data suggest that APPL is the first example of a modulator of the Wnt-PCP pathway specifically required for axon outgrowth.